Passive social media use and depression among college students during public health emergencies: a chain mediation approach - Wang, Lin; Li, Shuhe; Liu, Yajing; Cheng, Lu (Frontiers in Psychology, 2025)
IntroductionDespite growing evidence linking passive social media use to depression during public health emergencies, the underlying psychological mechanisms remain unclear. This study investigates the impact of passive social media use on depression among college students during the COVID-19 pandemic, specifically examining the mediating roles of vicarious traumatization and fear of missing out (FoMO).MethodsA structured survey was conducted among 322 college students. Data were collected through questionnaires and analyzed using SPSS 23.0. ANOVA, linear regression, and Bootstrap methods were employed to assess relationships and mediating effects in a model linking passive social media use, vicarious traumatization, FoMO, and depression.ResultsResults indicated that passive social media use did not directly predict depression, suggesting possible masking effects. However, passive social media use significantly predicted depression through partial mediation by vicarious traumatization and FoMO. Additionally, a chain mediation pathway was identified, in which vicarious traumatization and FoMO sequentially mediated the relationship between passive social media use and depression.DiscussionThese findings reveal how passive social media behaviors contribute to depression during public health crises by highlighting the cognitive-psychological processes involved. The study advances understanding of social media’s negative effects and provides actionable recommendations for mental health interventions during emergencies.